European Planning History in the 20th Century A Continent of Urban Planning - Welch Guerra, Max; Abarkan, Abdellah; Castrillo Romón, María A.; Pekár, Martin (Taylor & Francis, 2023)
The history of Europe in the 20th century is closely tied to the history of urban planning. Social and economic progress but also the brute treatment of people and nature throughout Europe were possible due to the use of urban planning and the other levels of spatial planning. Thereby, planning has constituted itself in Europe as an international subject. Since its emergence, through intense exchange but also competition, despite country differences, planning has developed as a European field of practice and scientific discipline. Planning is here much more than the addition of individual histories; however, historiography has treated this history very selective regarding geography and content. This book searches for an understanding of the historiography of planning in a European dimension. Scholars from Eastern and Western, Southern and Northern Europe address the issues of the public led production of city and the social functions of urban planning in capitalist and state-socialist countries. The examined examples include Poland and USSR, Czech Republic and Slovakia, UK, Netherlands, Germany, France, Portugal and Spain, Italy, and Sweden. The book will be of interest to students and scholars for Urbanism, Urban/Town Planning, Spatial Planning, Spatial Politics, Urban Development, Urban Policies, Planning History and European History of the 20th Century.